2011
DOI: 10.1016/j.neubiorev.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the cholinergic hypothesis in the development of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia affecting the elderly population today; however, there is currently no accurate description of the etiology of this devastating disorder. No single factor theory has been demonstrated as being causative; however, an alternative theory suggests that the interaction of multiple risk factors is responsible for AD. In this thesis I present data suggesting a neuroprotective role for acetylcholine during aging. Using a rat model of cholinergic depletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
276
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(284 citation statements)
references
References 360 publications
(568 reference statements)
3
276
0
5
Order By: Relevance
“…Such changes have led to the cholinergic hypothesis of memory dysfunction (Bartus, 2000;Craig et al, 2011). In fact, enhancing cholinergic function by continued use of cholinesterase inhibitor drugs is the currently accepted treatment against the onset of Alzheimer's disease (Anand et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes have led to the cholinergic hypothesis of memory dysfunction (Bartus, 2000;Craig et al, 2011). In fact, enhancing cholinergic function by continued use of cholinesterase inhibitor drugs is the currently accepted treatment against the onset of Alzheimer's disease (Anand et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…6 The causative role of Aβ is particularly compelling given the location and morphology of amyloid plaques in cases of amyloid angiopathy. However, other mechanisms not specific to aberrant Aβ have also been implicated in vascular pathology in AD such as inflammation, 19 thrombin, 20 and cholinergic dysfunction 21 all of which may coexist with tau pathology and/or neurodegeneration. While the data presented in this study does not directly discount the importance of these contributions, it does suggest that tau itself is not a driver of impaired CVR and supports the hypothesis of a fundamental role of amyloid pathology in the vascular abnormalities observed in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the causes of cognitive impairments vary, previous studies have suggested that alteration in cholinergic neurotransmission may play an important role in the disruption of learning and memory (Francis et al, 1999;Craig et al, 2011;Dumas and Newhouse, 2011). According to the cholinergic hypothesis, age-dependent cognitive decline is primarily related to impairment in cholinergic neurotransmission (Bartus et al, 1982;Coyle et al, 1983;Kirk et al, 1994).…”
Section: Introductionmentioning
confidence: 99%